What does a climate-resilient rural water supply system look like? An interdisciplinary approach to climate resilience mapping in Nepal - Nepal, Santosh; Aksha, S. K.; Pradhananga, Saurav; Aryal, Anil; Shrestha, R. N.; Shrestha, S.; Shrestha, P. (Wiley, 2025)
Climate change significantly affects the water, sanitation, and hygiene (WASH) services, especially in rural areas of developing countries like Nepal. Erratic rainfall, extreme precipitation, and rising temperatures are key challenges impacting water and sanitation, making these systems less resilient to a changing climate. Understanding the importance of climate-resilient WASH systems enables local authorities to assess and improve them through targeted interventions. In this research, we examined 180 rural water supply systems (RWSS) of Dailekh district located in the middle hills of Western Nepal and mapped their resilience across five domains. The domains include community capital, environment, infrastructure, institutional support and governance, and WASH management of the systems. The results show that 6% of the RWSS in the district have very low resilience, whereas only 11% have very high resilience. Most systems (76%) are classified as very low to medium-resilient systems, highlighting the urgent need for enhanced efforts to strengthen RWSS against the impact of climate change. Among the five domains assessed, institutional support and governance systems emerged as the weakest, closely followed by WASH management. In contrast, community capital stands out as the strongest domain across all surveyed systems. This article presents a flexible indicator-based approach for mapping the resilience of WASH systems in Nepal. This approach can be adapted to other areas of natural resource management by customizing indicators and domains tailored to local social-ecological contexts.